Optimizing Bandung City Government Public Services during the Covid-19 Pandemic - Anisa Putri Sari; Dede Sri Kartini (PERSPEKTIF, 2022)
Covid-19 presents new obstacles for all government sectors, including in terms of public services. The use of digital is the main medium in providing services to the community, so that the smart city concept is not only related to information technology, but can also be used as an effort to suppress the spread of the virus and minimize physical interactions related to the Covid-19 pandemic that is present in the community. The purpose of the study was to determine the optimization of public services in the city of Bandung due to the impact of the Covid-19 pandemic through the assessment of the dimensions of the quality of public services according to Zeithml, Berry, and Parasuraman including tangibles, reliability, responsiveness, assurance, and empathy. This study uses a type of literature research that is related to theoretical studies and cannot be separated from scientific literature. The results of this study are information about the government's efforts to provide services to the community by presenting the Sadayana application based on a study of the dimensions of the quality of public services as a place for digital literacy and collaboration with the people of Bandung, as well as an effort to suppress the spread of the Covid-19 virus by minimizing physical interaction.